Fundamental frequency switching strategy for grid‐connected cascaded H‐bridge multilevel inverter to mitigate voltage harmonics at the point of common coupling. Issue 12 (1st October 2016) - Hajizadeh, Mehdi; Fathi, Seyed Hamid
Abstract : Cascaded H‐bridge multilevel inverter with isolated dc sources is a suitable choice as an interface between grid and distributed generation (DG) sources. The main duty of the interface inverter is to adapt voltage of the grid and DG source while active and reactive power exchange is also controlled by it. Conventional fundamental frequency switching methods have been studied so far only for quality improvement of the inverter output voltage. However, for the grid‐connected applications, voltage quality at the point of common coupling (PCC) is more important than the inverter output voltage. This study presents a modified harmonic mitigation fundamental frequency switching method for the grid‐connected cascaded H‐bridge multilevel inverters. The goal is to calculate optimum switching angles of the inverter which satisfy the standard limits for the total harmonic distortion and harmonic contents of the voltage waveform at PCC considering specifications of the grid. This is also to be achieved with minimum required amount of the coupling impedance. Genetic algorithm optimisation program based on the modified switching method is employed for a sample system including a three‐phase cascaded H‐bridge seven‐level inverter connected to a harmonic polluted grid. Computer simulation using Simulink/MATLAB is performed, the results of which confirm effectiveness of the proposed method.